Fast and cost-effective production of transgenic potato microtubersof Gala and Milena varieties - Anna Nizkorodova; Alina Dmitrieva; Maria Suvorova; Bulat Iskakov (Journal of Applied Botany and Food Quality)
Potato microtubers play an important role in the technology of seed potato production, since they have great advantages in storage, transportation and mechanization due to their small size and weight. For research purposes, it is also often necessary to obtain microtubers, in particular when creating lines of transgenic potato plants. Unlike agricultural needs, research requires a small number of microtubers, but as fast as possible and with minimal financial costs. We propose a method for obtaining microtubers, which saves time for transferring in vitro studies to soil in 4-7 weeks compared to so called “high sucrose concentration” methods (high concentration of sucrose; reduced photoperiod). We designated the method as “2.5S” due to sucrose content (2.5%) in Murashige and Skoog medium which amount for each plant was reduced by approximately 3 times. That leads to a lack of nutrients and the rapid formation of microtubers. The proposed method was tested on two potato varieties and their transgenic lines; in case of one of the varieties, a reliable increase in the mass of microtubers by 1.6-3.6 times was recorded compared to the standard method of obtaining microtubers. The method is also cost-effective and does not require any additional labor costs from researchers.